Iron availability regulates growth, photosynthesis, and production of ferredoxin and flavodoxin in Antarctic sea ice diatoms - Pankowski, A; McMinn, A (Aquatic Biology, 2009)
Iron availability affects the growth of not only phytoplankton, but also sea ice diatoms.Iron availability had a clear effect on the growth rates of Fragilariopsis cylindrus and F. curta. Maximumgrowth rates were 0.57 dC1 for F. cylindrus and 0.28 dC1 for F. curta; Km (half-saturation growthconstant) was 0.51 10C12 and 1.3 10C12 M for F. cylindrus and F. curta, respectively. For both F.cylindrus and F. curta, Fv/Fm (quantum yield of fluorescence) was highest and lowest for the culturesgrown with the highest and lowest concentrations of iron, respectively. For both species there wasalso a reduction in both rETRmax (maximum relative electron transfer rate) and (photosynthetic efficiency)with decreasing iron concentration. For F. cylindrus grown with the least iron, rETRmax washalf of the iron-replete value, while was reduced by 65%. Changes in Ek (light-adaptation parameter)were not well defined. Immunoassays were developed for the proteins ferredoxin and flavodoxinin Antarctic pack ice. Iron availability had different effects on the expression of flavodoxin andferredoxin in the 2 Fragilariopsis species tested. Cultures of F. cylindrus grown at high iron concentrationproduced predominantly ferredoxin, with a small amount of flavodoxin. Ferredoxin wassequentially replaced by flavodoxin for cultures grown with less iron, although the response was nota simple switch from one protein to the other. The ability to produce ferredoxin is apparently absentin F. curta, with relatively constant levels of flavodoxin produced at all iron concentrations. Theseresults strongly imply that the presence of flavodoxin alone cannot be used as evidence of ironlimitedgrowth.